49 Combinatorial Pharmacogenomics to Guide Treatment Selection for Major Depressive Disorder: A Large, Blinded, Randomized Controlled Trial. (12th March 2019) - Greden, John F.; Rosthschild, Anthony J.; Thase, Michael; Dunlop, Boadie W.; DeBattista, DMH Charles; Conway, Charles R.; Forester, Brent P.; Mondimore, Francis M.; Shelton, Richard C.; Li, James; Gilbert, Alexa; Burns, Lindsey; et al.
Abstract: Background: Major depressive disorder (MDD) is a leading cause of disease burden worldwide, with lifetime prevalence in the United States of 17%. Here we present the results of the first prospective, large-scale, patient- and rater-blind, randomized controlled trial evaluating the clinical importance of achieving congruence between combinatorial pharmacogenomic (PGx) testing and medication selection for MDD. Methods: 1, 167 outpatients diagnosed with MDD and an inadequate response to ≥1 psychotropic medications were enrolled and randomized 1:1 to a Treatment as Usual (TAU) arm or PGx-guided care arm. Combinatorial PGx testing categorized medications in three groups based on the level of gene-drug interactions: use as directed, use with caution, or use with increased caution and more frequent monitoring. Patient assessments were performed at weeks 0 (baseline), 4, 8, 12 and 24. Patients, site raters, and central raters were blinded in both arms until after week 8. In the guided-care arm, physicians had access to the combinatorial PGx test result to guide medication selection. Primary outcomes utilized the Hamilton Depression Rating Scale (HAM-D17) and included symptom improvement (percent change in HAM-D17 from baseline), response (50% decrease in HAM-D17 from baseline), and remission (HAM-D17<7) at the fully blinded week 8 time point. The durability of patient outcomes was assessed at week 24. Medications were considered congruent with PGx test results if they were in the 'use as directed' or 'use with caution' report categories while medications in the 'use with increased caution and more frequent monitoring' were considered incongruent. Patients who started on incongruent medications were analyzed separately according to whether they changed to congruent medications by week8. Results: At week 8, symptom improvement for individuals in the guided-care arm was not significantly different than TAU (27.2% versus 24.4%, p=0.11). However, individuals in the guided-care arm were more likely than those in TAU to achieve remission (15% versus 10%; p<0.01) and response (26% versus 20%; p=0.01). Remission rates, response rates, and symptom reductions continued to improve in the guided-treatment arm until the 24week time point. Congruent prescribing increased to 91% in the guided-care arm by week 8. Among patients who were taking one or more incongruent medication at baseline, those who changed to congruent medications by week 8 demonstrated significantly greater symptom improvement (p<0.01), response (p=0.04), and remission rates (p<0.01) compared to those who persisted on incongruent medications. Conclusions: Combinatorial PGx testing improves short- and long-term response and remission rates for MDD compared to standard of care. In addition, prescribing congruency with PGx-guided medication recommendations is important for achieving symptom improvement, response, and remission for MDD patients. Funding Acknowledgements: This study was supported by Assurex Health, Inc.